Aesthetic Design as an Element of Service Innovation in New Technology-based Firms - Marina Candi (Copenhagen Business School (CBS), 2008)
The goals of this thesis are to examine new technology-based firms' use of aesthetic design as an element of service innovation and to explore potential relationships between aesthetic design and performance in this same context. There is a scarcity of research on aesthetic design as an element of service innovation, particularly in new technology-based firms. Because of this scarcity, a hybrid research strategy is appropriate and the empirical basis for this research encompasses multiple case studies, longitudinal quantitative data and evaluations by expert panels. The first phase of the research involves developing an operationalization of design that enables evaluation of aesthetic design as an element of innovation in technology-based firms. The second phase uses case research to explore the role and organization of aesthetic design in service innovation in new technology-based firms. The final phase explores relationships between aesthetic design and performance in the research context. Hypotheses are developed based on existing research, on one hand, and the results of the case research, on the other, and these hypotheses are tested using longitudinal survey-based data. The operationalization of design developed is a three-dimensional model consisting of functional design, visceral design and experiential design. Functional design is concerned with utility, features and delivery; visceral design is concerned with appealing to the human senses; and experiential design is concerned with message, symbols, culture, meaning, and emotional and sociological aspects. Visceral design and experiential design are combined to yield a formative measure of aesthetic design. The findings of the research are that new technology-based firms emphasize functional design over aesthetic design. Emphasis on aesthetic design is related positively with the importance of design in a firms' sector and founders' experience of sales and marketing, while it is negatively related with founders' technical education. In new technology-based firms, aesthetic design can be characterized as being used to exploit or counteract the characteristics that distinguish services from products, namely intangibility, inseparability, heterogeneity and perishability. The application of aesthetic design to counteract these characteristics is more prevalent than exploitation. Aesthetic design in new technology-based firms is found to be primarily silent, meaning that those performing design activities are mostly managers and technical staff engaged in design activities as part of their development efforts and without these activities necessarily being acknowledged as design. The findings regarding the relationship between aesthetic design and performance are that aesthetic design is positively related with competitive advantage, but that this relationship is dependent upon moderating factors. The effectiveness of aesthetic design in achieving competitive advantage through differentiation is found to differ depending on the current stage of commoditization. The greater the level of commoditization of a service the more effectively aesthetic design can be employed to improve competitive advantage. Furthermore, the findings suggest that the objectives underlying managers' decisions to use aesthetic design in service innovation are attracting new customers, improving firm image and/or retaining existing customers, and doing so at lower cost. Hypothesis testing using longitudinal survey-based data confirms that by and large these benefits are realized by new technology-based firms. This research makes a number of important contributions. The research focus lies in an area where there is little existing research and, thus, the operationalization of aesthetic design developed and the characterization of aesthetic design as an element of service innovation in new technology-based firms constitute important contributions. The characterization provides a picture of the prevalence, roles, organization and actors of aesthetic design in the research context. The research also contributes insight about the relationship between aesthetic design as an element of service innovation and performance of new technologybased firms. The research shows that various positive relationships exist but that they can be contingent upon existing conditions, which act as moderating factors.
hdl:10398/7132
Keywords: 650